2008
DOI: 10.1001/archderm.144.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Time Required for a Complete Skin Examination With and Without Dermoscopy

Abstract: To determine the time required to perform a complete skin examination (CSE) as a means of opportunistic screening for skin cancer both without and with dermoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…However, Zalaudek et al determined that that use of dermoscopy increased the median skin examination time by only 72 seconds. 64 Changes in melanocytic nevi over time can also be appreciated through side-by-side dermoscopic comparisons. Multiple studies have described monitoring nevi by comparison of serially taken dermoscopic images.…”
Section: Using Technology To Augment Early Melanoma Diagnosis Dermoscopymentioning
confidence: 99%
“…However, Zalaudek et al determined that that use of dermoscopy increased the median skin examination time by only 72 seconds. 64 Changes in melanocytic nevi over time can also be appreciated through side-by-side dermoscopic comparisons. Multiple studies have described monitoring nevi by comparison of serially taken dermoscopic images.…”
Section: Using Technology To Augment Early Melanoma Diagnosis Dermoscopymentioning
confidence: 99%
“…1d). Opponents of the method argue that examining dermoscopically all lesions would be time-consuming, but it has been shown that, with experience, dermoscopic examination adds very little extra time (2 min), especially if a polarized-light handheld instrument is used [11]. …”
Section: Look Basically At All Lesionsmentioning
confidence: 99%
“…In practical terms this means that combination of clinical evaluation and dermoscopy reduces the risk of false-negative diagnoses in melanoma [11,13] and reduces the possibility of false-positive cases referred to surgical excision, thus limiting the risk of removing pigmented lesions defined as suspicious on clinical examination but diagnosed as benign on histological examination [14]. In addition, combined clinical and dermoscopic examination is only slightly longer than clinical examination alone [15]. …”
Section: Discussionmentioning
confidence: 99%